Healthy eating a guide to nutrition. Food safety and disease prevention - Dean, Christine; Meridian Education Corporation; Film Media Group (New York : Meridian Education Corporation, 2011)
This program guides viewers through basic concepts of healthy eating and the principal nutrients that keep the body functioning properly. Dietary guidelines are also discussed.
[j.1]. Basic nutrition -- [j.2]. Nutrition and weight management -- [j.3]. Nutrition for sports and exercise -- [j.4]. Nutrition and eating disorders -- [j.5]. Food safety and disease prevention.
Title from container.
Volume numbers assigned by cataloger in the order of the publisher's item numbers.
Editor, Matt Bjur.
DVD format.
Keywords: Food Safety; Nutrition; Foodborne diseases